The oral health-related quality of life for individuals with fetal alcohol spectrum disorder - a cross-sectional study - Mohammad Saad Khawer; Keith Da Silva (BMC, 2023)
Abstract Background The oral health status of an individual can dramatically influence quality of life. Most individuals in Canada report having good oral health, however, this is not true for individuals with developmental disabilities such as fetal alcohol spectrum disorder (FASD). The purpose of this study is to compare the oral health-related quality of life (OHRQoL) of individuals with FASD and the general population in Saskatoon, Saskatchewan. Additionally, it aims to suggest ways to improve the oral health status and OHRQoL of these individuals. Methods For this cross-sectional study, the Oral Health Impact Profile-14 (OHIP-14) survey was used to assess the impact that oral health related problems can have on an individual's quality life. This study used a cross-sectional cohort study design with a survey methodology. The sample population compromised of 154 individuals with FASD along with a separate control group of 154 otherwise healthy adults. Results The results of the study showed that most of the individuals in the FASD group experienced pain in the past month. In both groups, cost was most frequently cited as a barrier to accessing care. The majority of individuals in the control group experienced a low impact across all OHIP-14 domains except for physical disabilities. However, in the FASD group, most individuals experienced higher impact scores in some of the categories including functional limitation, psychological discomfort, psychological disability and handicap. Conclusion The findings clearly demonstrate that there is a discernible effect on an individual's quality of life if they have poor oral health. In conclusion, further research is required to determine the most effective methods to improve the OHRQoL of individuals with disabilities.